Agribusiness and Innovation Systems in Africa - Larsen, Kurt; Kim, Ronald; Theus, Florian (World Bank, 2012)
The role of agriculture in sustainable development and poverty reduction for the vast majority of developing countries cannot be overemphasized. Forty-five percent of the developing world's population lives in households involved in agriculture, and twenty-seven percent in smallholder households, and most depend on agriculture for their livelihoods. The agricultural sector generates on average twenty-nine percent of gross domestic product (GDP), employs sixty-five percent of the labor force in agriculture-based countries, and is a key to generating overall growth. This book attempts to address these questions and challenges, by examining how agricultural innovation arises in four African countries, Ghana, Kenya, Tanzania, and Uganda, through agribusiness, public policies, and specific value chains for food staples, high value products, and livestock. Determinants of innovation are not viewed individually but within the context of a complex agricultural innovation system (AIS) involving many actors and interactions. The country reports are based on qualitative interviews with agribusiness representatives about their experiences in this area. The synthesis chapter preceding the country reports presents the main findings of the country reports, links common themes, and distills lessons learned.